2002
DOI: 10.1007/s00418-002-0428-9
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of original and regenerated skeletal muscle fibres in mdx dystrophic muscles

Abstract: The differentiation of both original muscle fibres and the regenerated muscle fibres following necrosis in mdx muscles was investigated using immunoblotting and immunocytochemical procedures. Before the onset of necrosis, postnatal skeletal muscles in mdx mouse differentiated well with only a slight delay in differentiation indicated by the level of developmental isoforms of troponin T. Prior to the onset of apparent myopathic change, both fast and slow skeletal muscle fibre types in mdx leg muscles also diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
(31 reference statements)
0
1
1
Order By: Relevance
“…On the basis of the developmental regulation of protein expression, these findings could also reflect slower muscular development in dystrophic EDL, leading to the persistent expression of the neonatal SERCA2a, which disappeared progressively during post-natal development. A recent study has also demonstrated a slight delay in the differentiation process of mdx muscles, indicated by the relative level of developmental isoforms of troponin T (Earnshaw et al 2002). In spite of the expression of the slow isoform of the SR Ca 2+ -pump in dystrophic EDL, our results do not indicate any shift in myosin expression to a slower isoform.…”
Section: Discussioncontrasting
confidence: 60%
“…On the basis of the developmental regulation of protein expression, these findings could also reflect slower muscular development in dystrophic EDL, leading to the persistent expression of the neonatal SERCA2a, which disappeared progressively during post-natal development. A recent study has also demonstrated a slight delay in the differentiation process of mdx muscles, indicated by the relative level of developmental isoforms of troponin T (Earnshaw et al 2002). In spite of the expression of the slow isoform of the SR Ca 2+ -pump in dystrophic EDL, our results do not indicate any shift in myosin expression to a slower isoform.…”
Section: Discussioncontrasting
confidence: 60%
“…), while other studies show a reverse trend (soleus: Earnshaw et al. ; vastus lateralis: Webster et al. ).…”
Section: Discussionmentioning
confidence: 84%
“…A fibra muscular em regeneração apresenta núcleo central com aspecto vesicular, citoplasma geralmente basófilo, refletindo alta síntese proteica e escassez de elementos contráteis, visível pelo número reduzido de estriações (Torres e Duchen, 1987). Já a fibra muscular completamente regenerada é caracterizada pela centro-nucleação, citoplasma eosinófilo e aumento da relação citoplasma/núcleo (Pastoret e Sebille, 1995;Earnshaw et al, 2002).…”
Section: Necrose E Regeneração No Músculo Distróficounclassified